Impairment of CDKL5 nuclear localisation as a cause for severe infantile encephalopathy. Issue 3 (9th November 2007) - Rosas-Vargas, H; Bahi-Buisson, N; Philippe, C; Nectoux, J; Girard, B; N'Guyen Morel, M A; Gitiaux, C; Lazaro, L; Odent, S; Jonveaux, P; Chelly, J; Bienvenu, T
Abstract : Mutations in the human X-linked cyclin-dependent kinase-like 5 ( CDKL5 ) gene have been shown to cause infantile spasms as well as Rett syndrome-like phenotype. To date, fewer than 20 different mutations have been reported. So far, no clear genotype–phenotype correlation has been established. We screened the entire coding region of CDKL5 in 151 affected girls with a clinically heterogeneous phenotype ranging from encephalopathy with epilepsy to atypical Rett syndrome by denaturing high liquid performance chromatography and direct sequencing, and we identified three novel missense mutations located in catalytic domain (p.Ala40Val, p.Arg65Gln, p.Leu220Pro). Segregation analysis showed that p.Arg65Gln was inherited from the healthy father, which rules out the involvement of CDKL5 in the aetiology of the phenotype in this patient. However, the de novo occurrence was shown for p.Ala40Val and p.Leu220Pro. The p.Ala40Val mutation was observed in two unrelated patients and represented the first recurrent mutation in the CDKL5 gene. For the two de novo mutations, we analysed the cellular localisation of the wild-type and CDKL5 mutants by transfection experiments. We showed that the two CDKL5 mutations cause mislocalisation of the mutant CDKL5 proteins in the cytoplasm. Interestingly these missense mutations that result in a mislocalisation of the CDKL5 protein are associated with severe developmental delay which was apparent within the first months of life characterised by early and generalised hypotonia, and autistic features, and as well as early infantile spasms.